Centennial energy digest : data from 1988 to 2008 - Guyadeen, Vashti G. (Trinidad and Tobago Chamber of Industry and Commerce Port of SpainTT, 2010)
Reviews the history of the energy sector in Trinidad and Tobago, highlights current issues and challenges facing the industry, looks at prospects for the future. Includes statistical data.